A configurational analysis of vocational education and training programmes: Types of education-employment linkage and their explanatory power - Ladina Rageth (ETH Zurich, KOF Swiss Economic Institute, 2018)
To deepen scholarly understanding of unfavourable youth labour market outcomes of vocational education and training (VET) programmes, this paper develops an empirical typology of VET programmes in developed countries. Building on a theoretical framework that draws on the theory of social systems, the paper analyses the linkage between actors from the education and employment systems in VET in preventing unfavourable youth labour market outcomes, such as unemployment and skills mismatch. Based on empirical data on the largest upper-secondary VET programmes in 18 countries or states within them, this paper identifies five real types of VET programmes. These real types represent different combinations of the education-employment linkage in any process phase of curriculum design, application, and updating. Importantly, this paper provides evidence that only real type VET programmes with a strong educationemployment linkage throughout the entire curriculum process are associated with high youth labour market integration.
Keywords: 330; Vocational Education and Training; Typology; Qualitative Comparative Analysis